2015
DOI: 10.1186/s12883-015-0464-4
|View full text |Cite
|
Sign up to set email alerts
|

A pilot cohort study of cerebral autoregulation and 2-year neurodevelopmental outcomes in neonates with hypoxic-ischemic encephalopathy who received therapeutic hypothermia

Abstract: BackgroundNeurodevelopmental disabilities persist in survivors of neonatal hypoxic-ischemic encephalopathy (HIE) despite treatment with therapeutic hypothermia. Cerebrovascular autoregulation, the mechanism that maintains cerebral perfusion during changes in blood pressure, may influence outcomes. Our objective was to describe the relationship between acute autoregulatory vasoreactivity during treatment and neurodevelopmental outcomes at 2 years of age.MethodsIn a pilot study of 28 neonates with HIE, we measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
93
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(94 citation statements)
references
References 36 publications
1
93
0
Order By: Relevance
“…In the current study, we extend our prior work 5,6,11,12 to validate the relationships between blood pressure, optimal MAP, and brain injury using qualitative and quantitative MRIs with the NRN brain injury score 2 and DTI MD scalars in neonates younger than 10 days. We hypothesized that both the NRN score and MD scalars would detect relationships between blood pressure deviation from optimal MAP and brain injury in newborns with HIE.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…In the current study, we extend our prior work 5,6,11,12 to validate the relationships between blood pressure, optimal MAP, and brain injury using qualitative and quantitative MRIs with the NRN brain injury score 2 and DTI MD scalars in neonates younger than 10 days. We hypothesized that both the NRN score and MD scalars would detect relationships between blood pressure deviation from optimal MAP and brain injury in newborns with HIE.…”
Section: Introductionmentioning
confidence: 86%
“…Inclusion criteria, which included a diagnosis of moderate to severe HIE based on the National Institute of Child Health and Human Development clinical trial of hypothermia 14 and gestational age ≥35 weeks, have been reported previously. 5,6,11 Only neonates who underwent a brain MRI on a 1.5 Tesla (T) scanner before the tenth day of life were eligible for the study. Exclusion criteria included congenital anomalies that could make cooling unsafe, coagulopathy with active bleeding, and absence of an arterial blood pressure catheter.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations